PREDIKSI PENURUNAN TIMBUNAN JALAN : STUDI KASUS: PENANGANAN DENGAN PRE-LOADING DI TEBING TINGGI, SUMATERA UTARA - Bartholomeus; Humisar Pasaribu (Jurnal Teknik Sipil, 2022)
One method of handling soil that can be done to speed up the consolidation process is to add a Pre-Loading embankment on top of the plan embankment. In addition, this handling is also carried out to achieve a reduction by the design load, so that the settlement of embankment after the construction period still meets the required criteria and standards. This study was conducted to obtain a comparison of the prediction of embankment settlement with the empirical method using CPT data and the prediction of settlement using the Asaoka Method. In addition, the results of the consolidation coefficient will also be compared which can be used to determine the right time for Pre-Loading excavation during the construction period. The data used are CPT test data in the field as well as laboratory test data and measurement data for the settlement plate settlement closest to the position of the CPT test. From the analysis carried out, it is obtained that the prediction of decline using the Asaoka method is smaller than the prediction of decline using the empirical method using CPT data. In addition, from the analysis, it was found that at locations HB-04 and SP 70, as well as HB-07 and SP 91, showed laboratory consolidation coefficient values (cv-Lab.) which were close to the consolidation coefficients of the Asaoka Method (cv-Asa.), while in HB -05 and SP 79 and HB-06 and SP 85 show a large difference in values. The average comparison of the cv-Lab. consolidation coefficients and CV-Asa. is 58.5%.